2007
DOI: 10.1016/j.physletb.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Small-x neutrino–hadron structure functions within the QCD color dipole picture

Abstract: We present an exploratory QCD analysis of the neutrino structure functions in charged current DIS using the color dipole formalism. The dipole cross sections are taken from recent phenomenological/theoretical studies in deep inelastic inclusive production. The theoretical predictions are compared to the available experimental results in the small-x region, which has never been considered so far.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…In addition, we predicted the nuclear ratios R 2 and R 3 and single out the size of nuclear effects in each case. It was found that small-x data show geometric scaling property for the boson-hadron cross section and the structure function F 2 is in agreement with the phenomenological implementation using the saturation models at the small-x region [1]. The structure functions xF νN 3 was discussed in detail, where the sea content described by the quantity ∆xF νN 3 is well described.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition, we predicted the nuclear ratios R 2 and R 3 and single out the size of nuclear effects in each case. It was found that small-x data show geometric scaling property for the boson-hadron cross section and the structure function F 2 is in agreement with the phenomenological implementation using the saturation models at the small-x region [1]. The structure functions xF νN 3 was discussed in detail, where the sea content described by the quantity ∆xF νN 3 is well described.…”
Section: Introductionsupporting
confidence: 65%
“…We quote Ref. [1] and Refs. [13,14] for the re-cent phenomenology using the color dipole picture in the case of CC neutrino interactions.…”
Section: Neutral Current Neutrino-nucleon Interaction At High Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been verified in Ref. [4] that the improvement is sizable at low-Q 2 . On the other hand, the large Q 2 region tends to be overestimated for x > 0.0175.…”
Section: B Gay Ducati M M Machado and M V T Machadomentioning
confidence: 74%
“…The CC DIS structure functions for neutrinonucleon scattering in the dipole picture [4] are related to the cross section for scattering of transversely and longitudinally polarized W ± bosons. That is,…”
Section: B Gay Ducati M M Machado and M V T Machadomentioning
confidence: 99%